Introduction: TWAIL - on praxis and the intellectual - Natarajan, Usha; Reynolds, John; Bhatia, Amar; Xavier, Sujith (Third World Quarterly, 2016)
This Special Issue emerges from the Third World Approaches to International Law (TWAIL) Cairo Conference in 2015 and addresses the conference theme, ‘On Praxis and the Intellectual’, by focusing on different aspects of the intellectual as a political actor. In introducing this Issue, we provide some background to the TWAIL network, movement, event, and publications; and delineate our own understandings of scholarly praxis as editors and conference organisers. Broadly, we understand praxis as the relationship between what we say as scholars and what we do – as the inextricability of theory from lived experience. Understood in this way, praxis is central to TWAIL, as TWAIL scholars strive to reconcile international law’s promise of justice with the proliferation of injustice in the world it purports to govern. Reconciliation occurs in the realm of praxis and TWAIL scholars engage in a variety of struggles, including those for greater self-awareness, disciplinary upheaval, and institutional resistance and transformation.
Keywords: Sujith Xavier